Effects of Nutritional Strategies on Glucose Homeostasis in Gestational Diabetes Mellitus: A Systematic Review and Network Meta-Analysis - Shixiao Jin; Liyan Sha; Jianli Dong; Jing Yi; Yang Liu; Zhongxian Guo; Bing Hu (Journal of Diabetes Research)
Background. Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy, and nutritional therapy is the basis of GDM treatment. However, the effects of different forms of nutritional supplementation on improving gestational diabetes are uncertain. Objective. We conducted a network meta-analysis to evaluate the effects of supplementation with different nutrients on glucose metabolism in women with GDM. Methods. We conducted a literature search using PubMed, EMBASE, and the Cochrane Library to identify randomized controlled trials (RCTs) comparing the differences between different nutritional strategies in women with GDM. The Cochrane tool was used to assess the risk of bias. Pairwise meta-analysis and network meta-analysis were used to compare and rank the effects of nutritional strategies for the improvement of fasting plasma glucose (FPG), serum insulin, and homeostasis model assessment-insulin resistance (HOMA-IR). Results. We included thirteen RCTs with a total of 754 participants. Compared with placebo, omega-3, magnesium, vitamin D, zinc, and probiotics were more beneficial for improving FPG, serum insulin, and HOMA-IR. Network analysis showed that vitamin D supplementation was superior to omega-3 (-3.64 mg/dL, 95% CI: -5.77 to -1.51), zinc (-5.71 mg/dL, 95% CI: -10.19 to -1.23), probiotics (-6.76 mg/dL, 95% CI: -10.02 to -3.50), and placebo (-12.13 mg/dL, 95% CI: -14.55 to -9.70) for improving FPG. Magnesium supplementation was more beneficial for decreasing serum insulin compared with probiotics (-5.10 μIU/mL, 95% CI: -9.32 to -0.88) and placebo (-7.80 μIU/mL; 95% CI-11.95, -3.65). Vitamin D was more effective than probiotics (-0.99, 95% CI: -1.84 to -0.14) and placebo (-1.80, 95% CI: -2.45 to -1.16) for improving HOMA-IR. Conclusion. Vitamin D supplementation significantly reduced FPG and regulated HOMA-IR. Magnesium supplementation was superior in decreasing serum insulin than supplementation with other nutrients. Nutrient supplementation seemed to have an effect on glucose homeostasis maintenance in patients with GDM and may be considered an adjunctive therapy.